Food Security Based on Population Factors in the Perspective of Public Governance: A Conceptual Study: Ketahanan Pangan Berbasis Faktor Kependudukan dalam Perspektif Tata Kelola Publik: Kajian Konseptual - Syafrullah Muhammad Deddy; Yuliansyah; Fadlurrahman -; Ikhtiara Seiren (Jurnal Pemerintahan dan Politik, 2026)
Purpose : This study aims to analyze the relationship between population factors and food security within the perspective of public governance through a conceptual approach. Design/methodology/approach : This study employs a qualitative approach with a conceptual paper design. Data were collected through literature review from relevant academic sources, including international and national journal articles. The analysis was conducted using descriptive-qualitative techniques by synthesizing theoretical concepts to develop an integrative conceptual framework. Findings : The findings indicate that population dynamics, such as population growth, density, urbanization, and demographic structure, significantly influence food demand, distribution, and consumption patterns. Public governance plays a mediating role in managing these dynamics through policy coordination, data-based decision-making, and adaptive governance mechanisms. The study proposes a conceptual model integrating population factors, public governance, and food security. Practical Implication : The study highlights the importance of strengthening data-driven public governance by integrating population data into food policy planning. It also emphasizes cross-sectoral coordination to ensure more targeted and effective food security policies. Originality/value : This study contributes to the literature by developing an integrative conceptual model that links population dynamics, public governance, and food security, offering a multidisciplinary perspective that is still limited in previous studies. Paper type : Conceptual Paper.